On the status of Isolophodon Roth, 1903 (Mammalia, Astrapotheria) and other little-known Paleogene astrapotheres from central Patagonia - Kramarz, Alejandro Gustavo (2013)
Most of the 16 currently recognized astrapothere genera are well known through numerous specimens preserving at least almost complete dentition. One of the exceptions is the enigmatic genus Isolophodon Roth, 1903, based on very scant and fragmentary materials from Paleogene levels of central Patagonia. This taxon was ruled out from almost all taxonomic lists, although its validity has not been discussed by subsequent authors. We herein re-describe and discuss the taxonomic status of the species of Isolophodon. The type species, I. cingulosus Roth, 1903, is characterized by having lower cheek teeth with a much reduced hypoflexid, resembling derived uruguaytheriines, but lower-crowned and with three lower premolars, as in the species of Astraponotus Ameghino, 1901. This is the only astrapothere nominal species attributable to the Tinguirirican South American Land Mammal Age (SALMA, Early Oligocene). Isolophodon aplanatus Roth, 1903 (Casamayoran and Mustersan SALMAs, middle Late Eocene) has proportionally more elongated lower molars and a less developed paraflexid than the type species. Isolophodon would represent an early diverging lineage of astrapotheriids, in which some dental features evolved convergently with the more derived uruguaytheriines. Additionally, we describe other fragmentary but very significant specimens from Paleogene localities in central Patagonia (Argentina) attributable to the following taxa: cf. Scaglia kraglievichorum (Barrancan? subage), based on a partial upper molar nearly 60% larger than the type of Scaglia kraglievichorum Simpson, 1957; Astrapotheriidae gen. et sp. 1 (Barrancan? Subage, Middle Eocene), based on an isolated upper molar larger than any other Eocene astrapothere; Astrapotheriidae gen. et sp. 2, based on five isolated upper cheek teeth from ‘‘La Cantera’’ (Gran Barranca, Early Oligocene), characterized by a large, isolated hypocone and accessory cusps on P3-P4. These taxa enlarge the known diversity of Paleogene astrapotheres and document novel evolutionary patterns for these mammals.